Afatinib Treatment for Advanced Mixed Non-small Cell Lung Cancer with CRISPLD2-NRG1 Fusion: A Case Report and Literature Review - Chunmei CHEN; Yang YU; Meijuan HUANG (Chinese Journal of Lung Cancer, 2024)
Lung cancer is the most common malignant disease and the leading cause of cancer death in China. Non-small cell lung cancer (NSCLC) accounts for over 80% of all lung cancers, and the probability of NSCLC gene mutations is high, with a wide variety of types. With the development of next-generation sequencing (NGS) detection technology, more and more patients with rare fusion gene mutations are detected. Neuregulin 1 (NRG1) gene is a rare oncogenic driver that can lead to activation of human epidermal growth factor receptor 3 (Her3/ErbB3) mediated pathway, resulting in tumor formation. In this article, we reported a case of mixed NSCLC with CRISPLD2-NRG1 fusion detected by RNA-based NGS, who responsed to Afatinib well after 1 month of treatment, and magnetic resonance imaging (MRI) showed shrinkage of intracranial lesions. Meanwhile, we also compiled previously reported NSCLC patients with NRG1 rare gene fusion mutation, in order to provide effective references for clinical diagnosis and treatment.